MENGENAL KENDALA GURU DALAM PEMBELAJARAN IPS DI SD - Putriana Ramadhani; Ayu Septiah Utami; Nadia Putri Nazari; Nopitasari; Susanti; Khoirunnisa; Muhammad Sofwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This journal discusses the challenges faced by teachers in teaching Social Sciences (IPS) at the elementary school level, focusing on SDN 112/I PERUMNAS. The study aims to identify various obstacles that affect the effectiveness of IPS learning, which is a crucial subject in shaping students' understanding of social, cultural, economic, and political environments. Using a qualitative descriptive approach, data were collected through in-depth interviews and direct observations. The results reveal six interrelated main challenges: low student interest in IPS material, limited media and supporting facilities, restricted learning time, inadequate textbooks and difficult language comprehension, lack of active participation from students, and high administrative burdens faced by teachers. These challenges significantly impact the achievement of IPS educational objectives. However, the study also finds that by implementing creative and innovative solutions, such as using simple media, contextual learning approaches, and developing independent teaching materials, these obstacles can be addressed. Therefore, ongoing support from various parties, including schools and educational policymakers, is essential to enhance the effectiveness of IPS learning in elementary schools.